KAJIAN TINGKAT KESEHATAN KOPERASI BERDASARKAN PERATURAN MENTERI KOPERASI DAN UKM N0. 14 TAHUN 2009 - Herdi, Henrikus; Asyik, Nur Fadjrih; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research are to recognize financial performance of Tuke Jung Credit Cooperation from health level aspect of credit cooperation period 2009-2011, know about anything problems that faced by credit cooperation, and give solution in problem solving that encountered by credit cooperation. The result of the research indicates that Tuke Jung Credit Cooperation experienced fluctuation in 2009 taken score 75,95 and included fairly well predicate, in 2010 taken score 82,7 and get good predicate, and in 2011 get score 73,95 get fairly well predicate. Fluctuation happened because cooperation own several problems that are greater risk, bigger debts of cooperation member and business expenses, big regional cross loan debt, unable to fulfill whole short term obligation, less of SHU, did not have limitation lending given to its members and only have one business that is loan and borrow the money. Therefore suggested Tuke Jung Credit Cooperation have policy by giving loan accompanied collateral in detail and clearly and selective in give loan to members, make limitation loan to member appropriate with own modal, should pressure business expenses and cooperation (interest of regional cross loan debt and risk cost), in long term must proposed interest decrease for regional loan cross. Keywords: Cooperation health level, financial performance, Regulation of Ministry of Cooperation and Small Enterprises Number 14 of 2009.